2013
DOI: 10.1097/mej.0b013e3283561261
|View full text |Cite
|
Sign up to set email alerts
|

Rotational thrombolelastometry produces potentially clinical useful results within 10 min in bleeding Emergency Department patients

Abstract: Eighteen percent of bleeding ED patients are coagulopathic using ROTEM including 25% of trauma patients. A 10-min ROTEM clot firmness (A10) is an excellent surrogate for MCF and allows a result to be obtained earlier than formal laboratory results and potentially within 10 min of the patient arriving in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…However, A5 and A10 need not be seen only as surrogates for MCF. To our knowledge, although the correlation of A5 and A10 with MCF has been studied , MCF has not yet been demonstrated as superior to A5 or A10 for predicting clinical outcome.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, A5 and A10 need not be seen only as surrogates for MCF. To our knowledge, although the correlation of A5 and A10 with MCF has been studied , MCF has not yet been demonstrated as superior to A5 or A10 for predicting clinical outcome.…”
Section: Discussionmentioning
confidence: 98%
“…We focused on A5, A10 and MCF using the EXTEM assay . We used scatter plots and Spearman correlation coefficients to examine the relationship of A5 and A10 with MCF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in different but related clinical settings, not included in this systematic review, have also investigated TEG® and ROTEM®. Two studies of ROTEM® in a mixed population with shock [ 66 ] and noncardiac surgery [ 67 ] demonstrated rapid and useful results to guide decisions in hemostatic resuscitation. Other studies with mixed trauma and nontrauma populations [ 68 - 71 ] demonstrated good ability of ROTEM® to predict the need for MT, a clinically useful outcome regardless of management approach (laboratory abnormality-directed versus blood-product ratio based).…”
Section: Discussionmentioning
confidence: 99%
“…Rotational thromboelastometry assay diagnostics utilize citrated whole blood with four independent measuring channels to allow a combination of appropriate assays . The EXTEM assay detects deficiencies of vitamin K‐dependent coagulation factors, fibrinogen, platelets and factor XIII.…”
Section: Methodsmentioning
confidence: 99%